Fashion school survival guide - Mbonu, Ezinma (Laurence King Publishing, 2015)
"This is an essential piece of kit for aspiring fashion designers, packed with technical tips, professional advice and inspirational quotes. From gathering research material and developing your design ideas to working with different fabrics, 100 nuggets of fashion wisdom will help you to make the most of your experience as a fashion student."